p53-Induced Autophagy Regulates Chemotherapy and Radiotherapy Resistance in Multidrug Resistance Cancer Cells - Shumei Ma; Dejuan Kong; Xinxin Fu; Lin Liu; Yi Liu; Chang Xue; Zhujun Tian; Lan Li; Xiaodong Liu (SAGE Publishing, 2021)
Background Multidrug resistance (MDR), a major problem in oncology therapy, limits the effectiveness of anticancer drugs. Although p53 functions as a tumor suppressor, the associations between p53 status, autophagy, and MDR are complicated and conditional. Method  In this report, p53-null human ovarian cancer cell line SKOV3 and its MDR phenotype SKVCR and human leukemia cell line CEM and its MDR phenotype CEM-VLB) (p53 mutant cell line) were used. Results  Compared to parental SKOV3, the mRNA and protein levels of MAPLC3-II and Beclin1 were higher in SKVCR cells. The inhibition of autophagy by 3-MA significantly sensitized SKVCR to VCR. Conversely, in drug-resistant leukemic cells CEM-VLB, the expressions of Beclin1 and MAPLC3-II were lower than CEM. CEM and CEM-VLB cells were treated with VLB .01 or 0.5 μg/mL, respectively, and the expression of p53 and autophagy up-regulated after VLB (.01 μg/mL) treatment in CEM cells. The percentage of S-phase and G2/M phase cells up-regulated significantly by .01 μg/mL VLB in CEM, which may relate to the status of p53 of CEM cells. A combination of radiation with 3-MA significantly increased apoptosis in CEM-VLB cells. Conclusion  Our discovery found that p53 is an important regulator controlling the balance between autophagy and MDR, as a potential drug target for ovarian cancer and leukemia.